Programmed death-ligand 1 expression in diffuse large B-cell lymphoma is associated with poor prognosis. Issue 1 (March 2023) - Al-Khateeb, Esraa; Abbas, Manal A.; Khader, Majd B.; Sughayer, Maher A.
Background: Programmed death-ligand 1 (PD-L1) expression in some tumors has prognostic implications. This work aims at investigating PD-L1 expression in diffuse large B-cell lymphoma (DLBCL) and to study its association with clinicopathological variables. Methods: The study consisted of 75 DLBCL patients who were cared for at the King Hussein Cancer Center during the period 2015–2018. The expression of PD-L1 in tumor tissue was assessed by immunohistochemistry using the anti-human PD-L1 (Clone 22C3) monoclonal antibody. The correlation between gender, age, clinical stage, pre-treatment-LDH level, tumor location, response to therapy, overall and event-free survival with PD-L1 expression was studied. Results: Six patients were excluded from further analysis as they were in relapse at the time of tissue sampling. The tumor proportion score (TPS) was ≥1% in 16/69 (23.2%) of DLBCL cases while the combined positive score (CPS) at a cut-off of ≥20 was observed in 23/69 (33.3%) cases. No significant difference in PD-L1 expression was found between germinal center B-cell-like (GCB) and non-GCB subtypes. Similarly, no differences in PD-L1 expression (at CPS ≥20 and TPS ≥1) were found between different genders, age groups, clinical stages, tumor location, and patient response to therapy. However, base-line lactate dehydrogenase was significantly elevated in patients with PD-L1 CPS ≥20. The overall survival was not significantly different between PD-L1-positive and -negative groups. On the other hand, the median event-free survival was higher in either of the PD-L1 TPS or CPS negative groups at 107months each versus 54 months in the PD-L1 positive group of either category. Conclusions: PD-L1 expression can predict event-free survival in DLBCL cases and therefore poor prognosis.